Preparation of graphene oxide siloxane hydrophobically modified nano-Mg(OH)2 and its flame retardant and antibacterial polylactic acid material

The nano-Mg(OH)2 was prepared and modified by siloxane and combined with graphene oxide, which solved the problem of low flame retardant efficiency and poor compatibility in PLA, achieving efficient flame retardant and antibacterial performance improvement.

CN116534880BActive Publication Date: 2025-04-25ANHUI YUANMENG BIO BASED MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310528921.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-11
Publication Date
2025-04-25
Estimated Expiration
2043-05-11

AI Technical Summary

Technical Problem

During the use of nano Mg(OH)2 as a flame retardant, there are problems such as low flame retardant efficiency, large addition amount, easy agglomeration of particles, and incompatible hydrophilicity with polylactic acid hydrophobicity, which affects its dispersion and interface binding in PLA.

Method used

NanoMg(OH)2 was prepared by double drop reverse precipitation method, and modified by amino-containing silane coupling agent to form siloxane-modified nano-Mg(OH)2. Then, graphene oxide is combined with modified nano Mg(OH)2 to form graphene oxide/siloxane modified nano Mg(OH)2, improving its compatibility and flame retardant properties in PLA.

Benefits of technology

By modifying nano Mg(OH)2, its compatibility and interface binding force with polylactic acid are improved, the flame retardant and antibacterial properties of flame retardant and antibacterial polylactic acid materials are significantly improved, and the amount of flame retardant is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004223790650000081
    Figure BDA0004223790650000081
Patent Text Reader

Abstract

The invention discloses a preparation method of hydrophobically modified nano magnesium hydroxide and a flame retardant and antibacterial polylactic acid material, and relates to the technical field of functional modification of polylactic acid. The invention adopts an amino-containing silane coupling agent to modify nano Mg(OH)2, thereby improving the interface bonding force and compatibility between the nano Mg(OH)2 and polylactic acid, and siloxane can also cooperate with the nano Mg(OH)2 to enhance the flame retardant effect; and the amphiphilicity of graphene oxide is utilized to effectively improve the compatibility between the modified nano Mg(OH)2 and a polylactic acid matrix, and the ‑COOH on the surface of the graphene oxide reacts with the ‑NH2 on the surface of the amino-modified nano Mg(OH)2 to form a covalent bond, thereby improving the modification fastness; and the flame retardant and antibacterial polylactic acid material can be obtained by functionally modifying polylactic acid with the graphene oxide / siloxane-modified nano Mg(OH)2 prepared by the invention.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention relates to the technical field of functional modification of polylactic acid, and in particular to preparation of graphene oxide siloxane hydrophobically modified nano Mg(OH)2 and a flame retardant and antibacterial polylactic acid material thereof. Background technology:

[0002] Polylactic acid (PLA) is an environmentally friendly polymer material with good biocompatibility and degradability. It is considered to be a green bio-based material with broad development prospects to replace petroleum-based polyester. However, the elemental composition (carbon, hydrogen, oxygen) and molecular chain structure (ester bonds are easily destroyed at high temperatures to generate volatile combustibles) of PLA determine that it has the same flammable defect as general polymers. The flammability of polylactic acid limits its application in certain special occasions. In addition, PLA itself does not have antibacterial properties. When used in food packaging films, biomedical materials or textile fiber materials, the uncontrolled growth of bacteria on PLA can seriously lead to adverse effects such as disease, discoloration and odor. The high flammability and lack of antibacterial groups of PLA limit its scope of application, especially those applications that require flame retardancy and antibacterial properties. Therefore, it is necessary to modify PLA to have flame retardant and antibacterial functions.

[0003] Nano-Mg(OH)2 is a nano-sized inorganic material with advantages such as good chemical stability and thermal stability, and is an ideal flame retardant material for polymer materials. In addition, nano-Mg(OH)2 also has broad-spectrum antibacterial properties and is a representative of inorganic antibacterial materials with good stability and long-lasting antibacterial properties. Therefore, nano-Mg(OH)2 can be used as a flame retardant and antibacterial agent to modify the flame retardant and antibacterial functions of PLA materials.

[0004] However, there are also the following problems when using nano Mg(OH)2 as a flame retardant: the flame retardancy of Mg(OH)2 is mostly produced by physical means, and the flame retardant efficiency is not high. A large amount of addition is required to achieve the desired flame retardant effect. Although the flame retardant efficiency can be improved to a certain extent by preparing it into nanoparticles, it still cannot meet the flame retardant demand of low addition amount; nano Mg(OH)2 particles are prone to agglomeration, affecting their dispersibility in PLA; since nano Mg(OH)2 is a hydrophilic inorganic material, and polylactic acid is a hydrophobic aliphatic polyester, nano Mg(OH)2 and PLA materials have poor compatibility and weak interface bonding. Summary of the invention:

[0005] The technical problem to be solved by the present invention is to provide a method for preparing graphene oxide / siloxane modified nano Mg(OH)2 and its application in the preparation of flame retardant and antibacterial polylactic acid materials, with the aim of improving the flame retardant and antibacterial properties of nano Mg(OH)2.

[0006] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:

[0007] The first object of the present invention is to provide a method for preparing nano Mg(OH)2, which comprises: slowly adding a magnesium salt solution and a NaOH solution containing a surfactant into a substrate solution in a double-drop manner, stirring for reaction, and filtering after the reaction is completed, washing with water, and drying to obtain nano Mg(OH)2.

[0008] Preferably, the substrate solution is prepared by adding ammonia water or NaOH to deionized water, and the concentration is 0-1.0 mol / L.

[0009] Preferably, the surfactant is polyethylene glycol or sodium stearate, and the amount used is 1-3% of the mass of NaOH.

[0010] Preferably, the concentration of the NaOH solution is 1.5-3.0 mol / L.

[0011] Preferably, the magnesium salt solution is prepared by adding MgCl2·6H2O or MgSO4·7H2O to deionized water, and the concentration is 1-2 mol / L.

[0012] Preferably, the stirring reaction temperature is 40-60°C.

[0013] The second object of the present invention is to provide nano-Mg(OH)2 obtained according to the aforementioned preparation method.

[0014] The third object of the present invention is to provide a method for preparing graphene oxide / siloxane modified nano-Mg(OH)2, comprising the following steps:

[0015] (1) dissolving a silane coupling agent in a solvent, adding the nano-Mg(OH)2, stirring and reacting, and obtaining a siloxane-modified nano-Mg(OH)2 dispersion;

[0016] (2) Ultrasonic exfoliation of graphene oxide in a solvent, then adding the siloxane-modified nano-Mg(OH)2 dispersion prepared in step (1), stirring for reaction, centrifugation after the reaction, washing with water, and drying to obtain graphene oxide / siloxane-modified nano-Mg(OH)2.

[0017] Preferably, the silane coupling agent is an amino-containing silane coupling agent, preferably γ-aminopropyltriethoxysilane or γ-aminopropyltrimethoxysilane.

[0018] Preferably, the mass ratio of the nano-Mg(OH)2 to the silane coupling agent is 1:(3-5).

[0019] Preferably, the amount of graphene oxide used is 10-20% of the total mass of the silane coupling agent and nano-Mg(OH)2.

[0020] Preferably, in step (1) and step (2), the temperature of the stirring reaction is 60 to 80°C.

[0021] Preferably, in step (1) and step (2), the solvent is an ethanol / water mixed solvent, and the volume fraction of ethanol is 10 to 30%.

[0022] The fourth object of the present invention is to provide graphene oxide / siloxane modified nano-Mg(OH)2 obtained according to the aforementioned preparation method.

[0023] The fifth object of the present invention is to provide the use of the graphene oxide / siloxane modified nano Mg(OH)2 as a flame retardant and antibacterial agent.

[0024] The sixth object of the present invention is to provide the application of the graphene oxide / siloxane modified nano Mg(OH)2 in the preparation of flame retardant and antibacterial polylactic acid materials.

[0025] The seventh object of the present invention is to provide a flame retardant and antibacterial polylactic acid material, comprising polylactic acid resin and the graphene oxide / siloxane modified nano-Mg(OH)2.

[0026] The mass proportion of the graphene oxide / siloxane modified nano Mg(OH)2 in the flame retardant and antibacterial polylactic acid material is 8-15%.

[0027] The eighth object of the present invention is to provide a method for preparing a flame retardant and antibacterial polylactic acid material, which comprises: uniformly mixing the dried polylactic acid resin and the graphene oxide / siloxane modified nano-Mg(OH)2, adding the mixture to a twin-screw extruder for extrusion granulation, and obtaining a flame retardant and antibacterial polylactic acid material.

[0028] Preferably, the twin-screw extruder has a melting temperature of 180-200° C. and a rotation speed of 200-250 rpm.

[0029] The flame retardant and antibacterial polylactic acid material may further include functional additives commonly used in the art, such as reinforcing agents, antioxidants, antistatic agents, UV protection agents, and the like.

[0030] The beneficial effects of the present invention are:

[0031] 1) The present invention adopts a double-drop reverse precipitation method to prepare nano-Mg(OH)2, which can ensure that the pH value of the reaction system is always higher than the isoelectric point, effectively avoiding the occurrence of coagulation during the reaction process; the double-drop method is also beneficial to reducing the supersaturation of the reaction system, which is beneficial to improving the dispersibility of the product.

[0032] 2) The present invention adopts an amino-containing silane coupling agent to modify nano-Mg(OH)2. On the one hand, the silane coupling agent can form a flexible deformation layer on the interface between nano-Mg(OH)2 and the polylactic acid polymer matrix. This deformation layer can relax the interfacial stress and improve the interfacial bonding force between nano-Mg(OH)2 and polylactic acid. On the other hand, siloxane, as a hydrophobic group, gives nano-Mg(OH)2 a certain hydrophobicity and improves the compatibility between nano-Mg(OH)2 and polylactic acid. Furthermore, siloxane has high thermal stability and can cooperate with nano-Mg(OH)2 to enhance the flame retardant effect.

[0033] 3) The present invention utilizes the amphiphilicity of graphene oxide to effectively improve the compatibility of modified nano-Mg(OH)2 and the polylactic acid matrix, and the -COOH on the surface of graphene oxide reacts with the -NH2 on the surface of amino-modified nano-Mg(OH)2 to form a covalent bond, thereby improving the modification fastness.

[0034] 4) Graphene oxide, siloxane, and nano-Mg(OH)2 themselves have certain flame retardant effects. These three substances are organically combined in the form of the present invention to perform flame retardant modification on PLA. Compared with adding these three substances separately, the graphene oxide / siloxane-modified nano-Mg(OH)2 prepared by the present invention has excellent compatibility and synergistic effect with the polylactic acid matrix. Specific implementation method:

[0035] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.

[0036] The material limiting oxygen index is tested according to standard GB / T 5454-1997 using a FAA type oxygen index meter.

[0037] The vertical combustion performance of the material was tested according to the standard ASTM D3801-2010, using the CZF-1 vertical combustion tester.

[0038] The antibacterial properties of the materials were tested according to the standard GB / T 20944-2008, and the inhibition rates against Escherichia coli and Staphylococcus aureus were measured.

[0039] Example 1

[0040] Add 20mL of 0.5mol / L NaOH aqueous solution (called substrate solution) to a four-necked flask. Prepare another 250mL of 2mol / L NaOH aqueous solution, add 0.2g polyethylene glycol, and mix and stir evenly (called solution 1). Prepare another 250mL of 1mol / L MgCl2 aqueous solution (called solution 2). Raise the temperature of the substrate solution to 40°C, slowly add solution 1 and solution 2 to the substrate solution in a double dropwise manner, and stir and react for 60 minutes. Centrifuge the resulting suspension, wash twice with deionized water, and dry in an oven at 80°C for 2h to obtain nano Mg(OH)2.

[0041] Add 60g of γ-aminopropyltriethoxysilane to 300mL of ethanol / water mixed solution (30mL of ethanol + 270mL of water), stir well, then add 12g of nano Mg(OH)2, continue stirring well, heat to 60℃ and react for 60min to obtain aminosiloxane-modified nano Mg(OH)2 dispersion.

[0042] 7.5g of graphene oxide was added to 150mL of ethanol / water mixed solution (15mL ethanol + 135mL water), ultrasonically treated for 60min, and exfoliated to obtain a dispersion of graphene oxide monolayer nanosheets. The graphene oxide monolayer nanosheet dispersion was added to the aminosiloxane modified nano Mg(OH)2 dispersion, the reaction system temperature was maintained at 60°C, and the reaction was stirred for 4h to obtain a graphene oxide / siloxane hydrophobically modified nano Mg(OH)2 dispersion. The dispersion was centrifuged and washed with clean water 3 times, placed in an oven at 60°C for 6h to obtain graphene oxide / siloxane hydrophobically modified nano Mg(OH)2.

[0043] The graphene oxide / siloxane hydrophobically modified nano-Mg(OH)2 and polylactic acid resin were dried in a vacuum oven at 60°C for 12 hours to remove moisture. After the dried 20g of graphene oxide / siloxane hydrophobically modified nano-Mg(OH)2 was evenly mixed with 180g of polylactic acid resin, it was added into a twin-screw extruder at 170°C and 200rpm for melt blending, extruded into granules, and then hot-pressed at 170°C into 2 mm thick strips.

[0044] Example 2

[0045] Add 50mL of 1mol / L ammonia solution (called substrate solution) to a four-necked flask. Prepare 250mL of 3mol / L NaOH solution, add 0.5g sodium stearate, mix and stir evenly (called solution 1). Prepare 250mL of 2mol / L MgCl2 solution (called solution 2). Raise the temperature of the substrate solution to 40°C, slowly add solution 1 and solution 2 to the substrate solution in a double dropwise manner, and stir and react for 60 minutes. Centrifuge the resulting suspension, wash twice with deionized water, and dry in an oven at 80°C for 2h to obtain nano Mg(OH)2.

[0046] Add 80g of γ-aminopropyltrimethoxysilane to 270mL of ethanol / water mixed solution (67.5mL of ethanol + 202.5mL of water), mix and stir evenly, then add 20g of nano Mg(OH)2, continue to stir evenly, heat to 60℃ and react for 60min to obtain aminosiloxane-modified nano Mg(OH)2 dispersion.

[0047] 15g of graphene oxide was added to 200mL of ethanol / water mixed solution (50mL ethanol + 150mL water), ultrasonically treated for 60min, and exfoliated to obtain a dispersion of graphene oxide monolayer nanosheets. The graphene oxide monolayer nanosheet dispersion was added to the aminosiloxane modified nano Mg(OH)2 dispersion, the reaction system temperature was maintained at 80°C, and the reaction was stirred for 4h to obtain a graphene oxide / siloxane hydrophobically modified nano Mg(OH)2 dispersion. The dispersion was centrifuged and washed with clean water 3 times, placed in an oven at 80°C for 4h to obtain graphene oxide / siloxane hydrophobically modified nano Mg(OH)2.

[0048] The graphene oxide / siloxane hydrophobically modified nano-Mg(OH)2 and polylactic acid resin were dried in a vacuum oven at 60°C for 12h to remove moisture. After the dried 24g of graphene oxide / siloxane hydrophobically modified nano-Mg(OH)2 was evenly mixed with 176g of polylactic acid resin, it was added into a twin-screw extruder at 180°C and 220rpm for melt blending, extruded into granules, and then hot-pressed at 180°C into 2 mm thick strips.

[0049] Example 3

[0050] Add 20mL of deionized water (called substrate solution) to a four-necked flask. Prepare 250mL of 1.5mol / L NaOH aqueous solution, add 0.45g of polyethylene glycol, and mix well (called solution 1). Prepare 250mL of 1mol / L MgSO4 aqueous solution (called solution 2). Raise the temperature of the substrate solution to 60°C, slowly add solution 1 and solution 2 to the substrate solution in a double dropwise manner, and stir and react for 30 minutes. Centrifuge the resulting suspension, wash twice with deionized water, and dry in an oven at 60°C for 4h to obtain nano Mg(OH)2.

[0051] Add 50g of γ-aminopropyltrimethoxysilane to 250mL of ethanol / water mixed solution (50m ethanol + 200mL water), mix and stir evenly, then add 10g of nano Mg(OH)2, continue to stir evenly, heat to 60℃ and react for 60min to obtain aminosiloxane-modified nano Mg(OH)2 dispersion.

[0052] 12g of graphene oxide was added to 240mL of ethanol / water mixed solution (48mL ethanol + 192mL water), ultrasonically treated for 60min, and exfoliated to obtain a dispersion of graphene oxide monolayer nanosheets. The graphene oxide monolayer nanosheet dispersion was added to the aminosiloxane modified nano Mg(OH)2 dispersion, the reaction system temperature was maintained at 60°C, and the reaction was stirred for 6h to obtain a graphene oxide / siloxane hydrophobically modified nano Mg(OH)2 dispersion. The dispersion was centrifuged and washed with clean water 3 times, placed in an oven at 80°C for 4h to obtain graphene oxide / siloxane hydrophobically modified nano Mg(OH)2.

[0053] The graphene oxide / siloxane hydrophobically modified nano-Mg(OH)2 and polylactic acid resin were dried in a vacuum oven at 60°C for 12h to remove moisture. After the dried 24g of graphene oxide / siloxane hydrophobically modified nano-Mg(OH)2 was evenly mixed with 176g of polylactic acid resin, it was added into a twin-screw extruder at 180°C and 220rpm for melt blending, extruded into granules, and then hot-pressed at 180°C into 2 mm thick strips.

[0054] Example 4

[0055] Add 50mL of 0.5mol / L ammonia solution (called substrate solution) to a four-necked flask. Prepare 250mL of 2mol / L NaOH solution, add 0.5g of sodium stearate, and mix well (called solution 1). Prepare 250mL of 1mol / L MgSO4 solution (called solution 2). Raise the temperature of the substrate solution to 40°C, slowly add solution 1 and solution 2 to the substrate solution in a double dropwise manner, and stir and react for 60 minutes. Centrifuge the resulting suspension, wash twice with deionized water, and dry in an oven at 80°C for 2h to obtain nano Mg(OH)2.

[0056] Add 60g of γ-aminopropyltriethoxysilane to 240mL of ethanol / water mixed solution (48mL of ethanol + 196mL of water), mix and stir evenly, then add 15g of nano Mg(OH)2, continue to stir evenly, heat to 60℃ and react for 60min to obtain aminosiloxane-modified nano Mg(OH)2 dispersion.

[0057] 12g of graphene oxide was added to 200mL of ethanol / water mixed solution (40mL ethanol + 160mL water), ultrasonically treated for 60min, and exfoliated to obtain a dispersion of graphene oxide monolayer nanosheets. The graphene oxide monolayer nanosheet dispersion was added to the aminosiloxane modified nano Mg(OH)2 dispersion, the reaction system temperature was maintained at 80°C, and the reaction was stirred for 4h to obtain a graphene oxide / siloxane hydrophobically modified nano Mg(OH)2 dispersion. The dispersion was centrifuged and washed with clean water 3 times, placed in an oven at 80°C for 4h to obtain graphene oxide / siloxane hydrophobically modified nano Mg(OH)2.

[0058] The graphene oxide / siloxane hydrophobically modified nano-Mg(OH)2 and polylactic acid resin were dried in a vacuum oven at 60°C for 12h to remove moisture. After the dried 24g of graphene oxide / siloxane hydrophobically modified nano-Mg(OH)2 was evenly mixed with 176g of polylactic acid resin, it was added into a twin-screw extruder at 180°C and 220rpm for melt blending, extruded into granules, and then hot-pressed at 180°C into 2 mm thick strips.

[0059] Embodiment 5-7

[0060] In Examples 5-7, the preparation method of graphene oxide / siloxane hydrophobically modified nano Mg(OH)2 is the same as that of Example 4, and the blending ratio of graphene oxide / siloxane hydrophobically modified nano Mg(OH)2 and polylactic acid resin is changed to prepare flame retardant and antibacterial polylactic acid materials with different contents of graphene oxide / siloxane hydrophobically modified nano Mg(OH)2. In Examples 5-7, the mass proportions of graphene oxide / siloxane hydrophobically modified nano Mg(OH)2 in the final prepared strip materials are 8%, 10% and 15%, respectively.

[0061] Comparative Example 1

[0062] In Control Example 1, the preparation method of nano-Mg(OH)2 is the same as that of Example 4, and nano-Mg(OH)2 is melt-blended with polylactic acid. The melt-blending ratio and conditions are the same as those of Example 4.

[0063] Comparative Example 2

[0064] In Comparative Example 2, the preparation method of aminosilicone-modified nano-Mg(OH)2 is the same as that of Example 4, and the obtained aminosilicone-modified nano-Mg(OH)2 is melt-blended with polylactic acid, and the melt-blending ratio and conditions are the same as those of Example 4.

[0065] Comparative Example 3

[0066] In Control Example 3, the preparation method of nano Mg(OH)2 is the same as that of Example 4, but it is directly modified with graphene oxide without modification with aminosiloxane, and the modification conditions of graphene oxide are the same as those of Example 4. The obtained graphene oxide modified nano Mg(OH)2 is melt blended with polylactic acid, and the melt blending ratio and conditions are the same as those of Example 4.

[0067] Comparative Example 4

[0068] The polylactic acid resin was directly added into a twin-screw extruder at 180° C. and a rotation speed of 220 rpm for melt blending, extruded into granules, and then heat-pressed at 180° C. to form a 2 mm thick strip material.

[0069] Table 1 Flame retardant and antibacterial properties of polylactic acid materials obtained in Examples 1-7 and Comparative Examples 1-4

[0070]

[0071] As shown in Table 1, nano Mg(OH)2 has excellent antibacterial properties, which is due to the fact that nano Mg(OH)2 may be able to directly penetrate the cell wall of bacteria, destroy the protein structure, and cause bacterial death; on the other hand, when nano Mg(OH)2 contacts bacteria, the nanoparticles will destroy the bacterial cell membrane and destroy the cells, playing an antibacterial role. Comparing the control example and the embodiment, it can be seen that by modifying nano Mg(OH)2 with graphene oxide and siloxane, the compatibility of nano Mg(OH)2 and PLA is improved, and the antibacterial property of functional modified PLA is further improved. When nano Mg(OH)2 is used as a flame retardant, a higher addition amount (30-50% or even higher) is usually required to give the material an ideal flame retardant effect. It can be clearly seen from the control example 3 that when nano Mg(OH)2 is directly melt-blended with PLA, at this addition amount (12%), the improvement of the flame retardant properties of PLA is limited, the oxygen index is slightly improved, and there is no grade of vertical combustion. When the nano-Mg(OH)2 is modified by graphene oxide and siloxane, the obtained graphene oxide / siloxane hydrophobically modified nano-Mg(OH)2 has a significant effect on improving the flame retardant properties of PLA. As shown in Examples 1-4, this improvement effect is positively correlated with the degree of modification. When the addition amount of the graphene oxide / siloxane hydrophobically modified nano-Mg(OH)2 is 15% (Example 7), the flame retardant effect is excellent.

[0072] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing graphene oxide / siloxane modified nano-Mg(OH)2, characterized in that: The following steps are involved: (1) dissolving a silane coupling agent in a solvent, adding nano-Mg(OH)2, and stirring to react to obtain a siloxane-modified nano-Mg(OH)2 dispersion; (2) ultrasonically exfoliating the graphene oxide in a solvent, then adding the siloxane-modified nano-Mg(OH)2 dispersion prepared in step (1), stirring for reaction, centrifuging after the reaction, washing with water, and drying to obtain graphene oxide / siloxane-modified nano-Mg(OH)2; The silane coupling agent is an amino-containing silane coupling agent.

2. The preparation method according to claim 1, characterized in that The preparation method of the nano Mg(OH)2 is as follows: a magnesium salt solution and a NaOH solution containing a surfactant are slowly added to a substrate solution in a double-drop manner, stirred for reaction, and after the reaction is completed, filtered, washed with water, and dried to obtain the nano Mg(OH)2.

3. The preparation method according to claim 2, characterized in that: The substrate solution is prepared by adding ammonia water or NaOH to deionized water, and the concentration is 0-1.0 mol / L.

4. The preparation method according to claim 2, characterized in that: The surfactant is polyethylene glycol or sodium stearate, and the dosage is 1-3% of the mass of NaOH.

5. The preparation method according to claim 2, characterized in that: The concentration of the NaOH solution is 1.5-3.0 mol / L.

6. The preparation method according to claim 2, characterized in that: The magnesium salt solution is prepared by adding MgCl2·6H2O or MgSO4·7H2O to deionized water, and the concentration is 1-2 mol / L.

7. The preparation method according to claim 2, characterized in that: The temperature of the stirring reaction is 40-60°C.

8. The preparation method according to claim 1, characterized in that: The silane coupling agent is γ-aminopropyltriethoxysilane or γ-aminopropyltrimethoxysilane.

9. The preparation method according to claim 1, characterized in that: The mass ratio of the nano-Mg(OH)2 to the silane coupling agent is 1: (3-5).

10. The preparation method according to claim 1, characterized in that: The amount of graphene oxide used is 10-20% of the total mass of the silane coupling agent and nano-Mg(OH)2.

11. The preparation method according to claim 1, characterized in that: In step (1) and step (2), the temperature of the stirring reaction is 60-80° C.; the solvent is an ethanol / water mixed solvent, and the volume fraction of ethanol is 10-30%.

12. Graphene oxide / siloxane-modified nano-Mg(OH)2 obtained according to the preparation method according to any one of claims 1 to 11.

13. Use of the graphene oxide / siloxane modified nano-Mg(OH)2 according to claim 12 as a flame retardant and antibacterial agent.

14. Use of the graphene oxide / siloxane modified nano-Mg(OH)2 according to claim 12 in the preparation of flame retardant and antibacterial polylactic acid materials.

15. A flame retardant and antibacterial polylactic acid material, comprising polylactic acid resin and the graphene oxide / siloxane modified nano-Mg(OH)2 according to claim 12.

16. The flame retardant and antibacterial polylactic acid material according to claim 15, characterized in that: The mass proportion of the graphene oxide / siloxane modified nano Mg(OH)2 in the flame retardant and antibacterial polylactic acid material is 8-15%.

17. The method for preparing the flame retardant and antibacterial polylactic acid material according to claim 15, characterized in that: The dried polylactic acid resin and the graphene oxide / siloxane modified nano-Mg(OH)2 are mixed evenly and then added into a twin-screw extruder for extrusion granulation to obtain a flame-retardant and antibacterial polylactic acid material.

18. The method for preparing the flame retardant and antibacterial polylactic acid material according to claim 17, characterized in that: The twin-screw extruder has a melting temperature of 180-200°C and a rotation speed of 200-250 rpm.

Citation Information

Patent Citations

  • Preparation of nano flame-retardant and smoke-suppressing agent and flame-retardant and smoke-suppressing polylactic acid fiber material

    CN116023408A

  • Preparation method of hydrophobic ultrafine nanometer fire retardant magnesium hydroxide

    CN1869154A